(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
West African countries Togo and Sierra Leone face numerous ecological and managerial challenges in the context of globalization and cultural diversity. This study examines issues related to SMEs, e-commerce logistics, and intercultural management as key factors influencing sustainable development. Despite their economic potential, SMEs in both countries encounter limited access to financing, weak infrastructure, and insufficient managerial skills. Meanwhile, the growing e-commerce sector is hindered by last-mile delivery issues, lack of proper address systems, and high transportation costs. In the context of intercultural interaction and trade with Russia, China, the U.S., the EU, and other African countries, difficulties arise in adapting management practices, which affect international cooperation and investment attraction. The paper proposes strategies for sustainable development, including digitalization, change management approaches, promotion of «green» technologies, professional training enhancement, and integration of local and regional supply chains. It also emphasizes the importance of creating conditions for the sustainable use of natural resources and implementing innovative solutions and decision-making processes related to the rational use and development of ecological resources, biodiversity conservation, practical implementation of ecocity concepts, waste management, efficient energy utilization, agricultural development, and more. These strategies support Sustainable Development Goals-2030 (SDGs), particularly SDG 8 (Decent Work), SDG 9 (Industry and Innovation), SDG 11 (Sustainable Cities, Eco-Cities), and SDG 17 (Partnerships). The research is based on current data on the countries’ integration into global and regional economic processes.